Factors Associated With Self‐Report Symptom Screening Adherence in Pediatric Cancer Patients - L. Lee Dupuis; Emily Vettese; Catherine Aftandilian; Vibhuti Agarwal; Christina Baggott; Scott M. Bradfield; Nicole Crellin‐Parsons; David R. Freyer; Kara M. Kelly; Allison A. King; Wade Kyono; Ramamoorthy Nagasubramanian; et al. (Cancer Medicine, 2025)
ABSTRACT Introduction Objective was to describe the association between baseline characteristics and the number of Symptom Screening in Pediatrics Tool (SSPedi) assessments completed over an 8‐week period. Methods This was a sub‐analysis of a cluster randomized controlled trial among 10 sites that were randomized to the intervention group. Participants were English‐ or Spanish‐speaking pediatric patients 8–18 years of age newly diagnosed with cancer. Participants were prompted to complete SSPedi three times weekly for 8 weeks. The outcome was the number of SSPedi assessments completed during the 8‐week period. Factors associated with the number of assessments were determined using mixed effects Poisson regression. Results At the 10 intervention sites, 216 patients were included in the analysis. Among these participants, 129 (59.7%) were male, 112 (51.9%) were white, and 83 (38.4%) were Hispanic. The number of SSPedi assessments was significantly higher for participants 11–14 years (rate ratio (RR) 1.13, 95% confidence interval (CI) 1.02–1.25) and 15–18 years (RR 1.15, 95% CI 1.04–1.27) compared to 8–10 years. Participants completed more SSPedi assessments if they were Asian compared to white (RR 1.27, 95% CI 1.10–1.46), non‐Hispanic compared to Hispanic (RR 1.15, 95% CI 1.04–1.28) and from families with a household income ≥$60,000 (RR 1.12, 95% CI 1.03–1.21). Participants completed fewer SSPedi assessments if they had solid tumors compared to leukemia (RR 0.91, 95% CI 0.84–0.99). Conclusion Adherence to three‐times weekly SSPedi varied by age, race, ethnicity, cancer diagnosis, and family income. This information may facilitate interventions to support routine symptom screening in clinical practice. Trial Registration: NCT04614662.